A comprehensive utilization method of aluminum-zinc smelting tailings
Patent Information
- Application Number
- CN202611257684.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-19
- Publication Date
- 2026-10-16
AI Technical Summary
本技术方案将镀铝锌渣与热浸镀锌渣进行耦合,采用不少于两层筛选并获取下层筛网表面的筛选物,在体积误差小的情况下,分为轻重质,调控镀铝锌渣的铝锌比,轻质组满足复合铝锌铁混凝剂的高铝含量需求,重质组提升的锌铝比值作用于热浸镀锌渣回收过程中的预熔体,利用铝降低热浸镀锌渣回收过程中锌池对铁的溶解质量,此项符合方法满足复合铝锌铁混凝剂的高铝含量需求同时提高热浸镀锌渣回收的锌纯度。
Smart Images

Figure CN122918336A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid waste recycling technology, specifically a method for the comprehensive utilization of tailings from aluminum and zinc smelting. Background Technology
[0002] Aluminized zinc slag (GAS) is mainly composed of aluminum and zinc, with zinc content below 40% and aluminum content above 50%. Zinc is difficult to extract due to its low content, but the high proportion of aluminum can be used to prepare composite aluminum-zinc-iron coagulants, thereby utilizing solid waste.
[0003] Hot-dip galvanizing is a relatively effective and convenient method for steel corrosion protection. my country's zinc production exceeds one million tons annually, with approximately one million tons used for hot-dip galvanizing, generating over 200,000 tons of galvanizing dross. Hot-dip galvanizing dross consists of dissolved iron and molten zinc in the zinc bath. The mass fraction of dissolved Fe in the zinc bath is affected by Al; therefore, a pre-melting starter is prepared before treating the hot-dip galvanizing dross, and Al is intentionally added to this starter to reduce the mass of dissolved Fe.
[0004] In summary, it can be understood that aluminized zinc slag, due to its zinc content being below 40%, is difficult to extract and is therefore used to manufacture coagulants for secondary utilization. Hot-dip galvanized slag, on the other hand, intentionally has Al added to reduce Fe dissolution. Therefore, to reduce Al waste, aluminized zinc slag (GAS) is coupled with hot-dip galvanized iron slag to further improve utilization efficiency. Summary of the Invention
[0005] The purpose of this invention is to provide a comprehensive utilization method for aluminum-zinc smelting tailings. This method couples aluminized zinc slag with hot-dip galvanized slag, employs at least two layers of screening, and obtains the sieving material from the surface of the lower screen. With minimal volume error, the material is divided into light and heavy phases. The aluminum-zinc ratio of the aluminized zinc slag is controlled. The light phase meets the high aluminum content requirement of the composite aluminum-zinc-iron coagulant, while the increased zinc-aluminum ratio of the heavy phase acts on the pre-melted material during the hot-dip galvanized slag recovery process. Aluminum is used to reduce the dissolution of iron in the zinc bath during the hot-dip galvanized slag recovery process. This method satisfies the high aluminum content requirement of the composite aluminum-zinc-iron coagulant while improving the zinc purity of the recovered hot-dip galvanized slag, thus solving the problems mentioned in the background art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for comprehensive utilization of tailings from aluminum-zinc smelting includes: Step S1, which is not less than once: After crushing the aluminum-zinc slag, it is screened through screens of different apertures. The aluminum-zinc tailings between the two screens are grouped into light group and heavy group according to the weight. Aluminized zinc slag contains more than 50% aluminum, less than 40% zinc, and very little iron. After crushing, the volume difference of the aluminized zinc slag is reduced. The filtration effect of at least two screens further minimizes the volume tolerance of the crushed aluminized zinc slag above the screens. However, the zinc and aluminum content is not entirely consistent in each region, resulting in different masses in each crushed particle. Since zinc has a much greater mass than aluminum, the heavier particles have a higher zinc content than the lighter particles, allowing for adjustment of the aluminum-zinc ratio based on the light and heavy particles. A high aluminum content satisfies the requirements for preparing the composite aluminum-zinc-iron coagulant.
[0007] In the preparation process of composite aluminum-zinc-iron coagulant, the aluminized zinc slag can be crushed into medium-sized blocks or small pieces. Therefore, it can undergo multiple crushing and screening processes to gradually separate the light and heavy components. The more crushing stages and the smaller the particle size, the higher the accuracy of light and heavy component separation. Specific adjustments can be made according to requirements. The specific method for preparing composite aluminum-zinc-iron coagulant is as follows: S2: Place the light component in a container and add 8%-15% HCl and 20%-40% H2SO4. Immerse it in a 70-100℃ water bath constant temperature shaker for 1-3 hours. Filter the solution using ashless quantitative filter paper in the range of 40-50℃ to obtain a colorless filtrate. S3: Add 0.2%-0.8% NaOH to the colorless filtrate in step S2 and stir rapidly. The polymerization temperature is 30-50℃, the pH value is 2.5-3, and the time is not less than 2-72h. A light yellow-brown liquid is obtained and dried and ground to obtain a powdered solid. The simulation experiment parameters are as follows: The wastewater composition consisted of 1.5 mg / L acidic deep blue, 50 mg / L kaolin, and tap water. These three substances were mixed and allowed to settle. The supernatant was collected as wastewater, with a pH of 7.65, a color intensity of 250 times, a turbidity of 100 NTU, and a w(COD) Cr ) = 300mg / L, temperature: 17℃.
[0008] A beaker stirring experiment was conducted, with a coagulant concentration of 10 g / L, calculated as Al. Turbidity and COD were measured using a turbidity meter, a rapid COD analyzer, and a colorimeter. Cr and color.
[0009] The optimal dosage of composite aluminum-zinc-iron is much lower than that of polyaluminum chloride. Both composite aluminum-zinc-iron and polyaluminum chloride enter the re-stabilization stage, but the gap between the optimal and re-stabilization dosage of composite aluminum-zinc-iron is much larger than that of polyaluminum chloride. Therefore, composite aluminum-zinc-iron has a greater buffering capacity for changes in dosage, while polyaluminum chloride has a narrow dosage range to cope with changes in water quality and has a smaller adaptability when treating water samples with frequent changes in water quality.
[0010] S4: Add the heavy mass to the crucible as the starting material, and add hot-dip galvanizing slag containing iron and zinc into the crucible. After melting at 680℃ and standing for 30 minutes, drain the zinc to obtain crude zinc ingots.
[0011] The heavy feedstock has an increased zinc content and a decreased aluminum content, with zinc used in hot-dip galvanizing slag. Since hot-dip galvanizing slag consists of dissolved iron and molten zinc in the zinc bath, the heavy feedstock acts as a melt initiator for the slag. Because the amount of melt initiator is much smaller than the amount of molten material added, the proportion of melt initiator in the entire molten liquid can be reduced by increasing the amount of molten material, thereby controlling the aluminum content in the entire molten liquid. The higher the aluminum content in the molten pool, the lower the solubility of iron in the liquid phase. Therefore, dissolving aluminum in the zinc bath can control the iron content in the zinc bath at a low level. Although the zinc content in the heavy feedstock is increased, it is still lower than the zinc content in the hot-dip galvanizing slag, which contains approximately 79% zinc. Therefore, the high proportion of zinc in the heavy feedstock can also be extracted during the hot-dip galvanizing slag treatment process, while simultaneously reducing the amount of iron dissolved in the zinc bath.
[0012] As a further embodiment of the present invention: the light yellow-brown liquid obtained in step S3 is dried in an oven at 100°C for no less than 25 hours.
[0013] As a further aspect of the present invention: In step S1, the light and heavy powder groups are separated by air classification. When the particle size of the aluminized zinc slag is too small to be easily screened, the average particle size is obtained through sampling and estimation. The air force is adjusted to drive the light powder to move, the heavy powder to fall, or other relative movements of the light and heavy powders, so that the light powder is separated from the powder pile. The smaller the particle size of the aluminized zinc slag, the better the screening effect.
[0014] As a further embodiment of the present invention: the zinc slag that has passed through the last sieve is combined with the light material group to perform step S2.
[0015] As a further aspect of the present invention: in step S1, the light group and the heavy group are calculated using the average mass of a single group of particles as the unit, and the light group or the heavy group is divided by a value not less than the average value.
[0016] As a further aspect of the present invention, it includes S11: after crushing the aluminized zinc slag, the lightweight components are compressed into spheres of the same volume through a pelletizing process, and the lightweight spheres are further distinguished by mass according to the method of claim 2, and the distinguished spheres are placed separately.
[0017] After the above steps, the small-particle-size aluminum-zinc slag is processed in smaller sizes, and the volume error has a greater impact on the quality error. When it is difficult to control the volume uniformity, the pressing and pelletizing process can be used to press the powder of the same volume into the same volume. On the one hand, it is convenient for storage and use, and on the other hand, it can make the volume more standardized and improve the differentiation accuracy.
[0018] As a further aspect of the present invention: in step S4, a covering agent is added to the crucible molten pool for protection, and the covering agent is ZnCl2.
[0019] As a further embodiment of the present invention, step S5 is also included: adding the zinc slurry from step S4 into a pit furnace, adding a covering agent for protection, the covering agent being ZnCl2, and letting it stand at 450°C for 30 minutes to improve the quality of crude zinc.
[0020] Compared with the prior art, the beneficial effects of the present invention are: This technical solution couples aluminized zinc slag with hot-dip galvanized slag. It employs at least two screening layers and obtains the slag from the surface of the lower screen. With minimal volume error, the slag is divided into light and heavy components. The aluminum-zinc ratio of the aluminized zinc slag is controlled. The light component meets the high aluminum content requirement of the composite aluminum-zinc-iron coagulant. The increased zinc-aluminum ratio of the heavy component acts on the pre-melted material in the hot-dip galvanized slag recovery process. Aluminum is used to reduce the dissolution of iron in the zinc bath during the hot-dip galvanized slag recovery process. This method meets the high aluminum content requirement of the composite aluminum-zinc-iron coagulant while improving the zinc purity of the recovered hot-dip galvanized slag. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 Chart showing the turbidity removal rate of the composite aluminum-zinc-iron coagulant; Figure 2 COD of composite aluminum-zinc-iron coagulant Cr Removal rate chart; Figure 3 Chart showing the color removal rate of composite aluminum-zinc-iron coagulant; Detailed Implementation
[0023] Please see Figure 1-3 : This embodiment includes: Step S1, which is not less than once: After crushing the aluminum-zinc slag, it is screened through screens of different aperture sizes. The aluminum-zinc tailings between the two screens are grouped into light and heavy groups according to their weight.
[0024] Aluminized zinc slag contains more than 50% aluminum, less than 40% zinc, and very little iron. After crushing, the volume difference of the aluminized zinc slag is reduced. The filtration effect of at least two screens further minimizes the volume tolerance of the crushed aluminized zinc slag above the screens. However, the zinc and aluminum content is not entirely consistent in each region, resulting in different masses in each crushed particle. Since zinc has a much greater mass than aluminum, the heavier particles have a higher zinc content than the lighter particles, allowing for adjustment of the aluminum-zinc ratio based on the light and heavy particles. A high aluminum content satisfies the requirements for preparing the composite aluminum-zinc-iron coagulant.
[0025] In the preparation process of composite aluminum-zinc-iron coagulant, the aluminized zinc slag can be crushed into medium-sized blocks or small pieces. Therefore, it can undergo multiple crushing and screening processes to gradually separate the light and heavy components. The more crushing stages and the smaller the particle size, the higher the accuracy of light and heavy component separation. Specific adjustments can be made according to requirements. The specific method for preparing composite aluminum-zinc-iron coagulant is as follows: S2: Place the light component in a container and add 8%-15% HCl and 20%-40% H2SO4. Immerse it in a 70-100℃ water bath constant temperature shaker for 1-3 hours. Filter the solution using ashless quantitative filter paper in the range of 40-50℃ to obtain a colorless filtrate. S3: Add 0.2%-0.8% NaOH to the colorless filtrate in step S2 and stir rapidly. The polymerization temperature is 30-50℃, the pH value is 2.5-3, and the time is not less than 2-72h. The resulting light yellow-brown liquid is dried in an oven at 100℃ for not less than 25h and then ground to obtain a powdered solid.
[0026] Please see Figures 1-3 , Figures 1-3 The results show a comparison of the wastewater treatment effects of composite aluminum-zinc-iron coagulant with polyaluminum chloride at different dosages.
[0027] The simulation experiment parameters are as follows: The wastewater composition consisted of 1.5 mg / L acidic deep blue, 50 mg / L kaolin, and tap water. These three substances were mixed and allowed to settle. The supernatant was collected as wastewater, with a pH of 7.65, a color intensity of 250 times, a turbidity of 100 NTU, and a w(COD) Cr ) = 300mg / L, temperature: 17℃.
[0028] A beaker stirring experiment was conducted, with a coagulant concentration of 10 g / L, calculated as Al. Turbidity and COD were measured using a turbidity meter, a rapid COD analyzer, and a colorimeter.Cr and color.
[0029] pass Figures 1-3 It can be seen that the optimal dosage of composite aluminum-zinc-iron is much lower than that of polyaluminum chloride. Both composite aluminum-zinc-iron and polyaluminum chloride enter the re-stabilization stage, but the gap between the optimal and re-stabilization dosage of composite aluminum-zinc-iron is much larger than that of polyaluminum chloride. Therefore, composite aluminum-zinc-iron has a greater buffering capacity for changes in dosage, while polyaluminum chloride has a narrow dosage range to cope with changes in water quality and has a smaller adaptability when treating water samples with frequent changes in water quality.
[0030] S4: Add the heavy mass to the crucible as the starting material, and add hot-dip galvanizing slag containing iron and zinc into the crucible. After melting at 680℃ and standing for 30 minutes, the zinc is leaked out. Add a covering agent, ZnCl2, to the molten pool in the crucible for protection.
[0031] Step S5: Add the zinc slurry from step S4 to the pit furnace, add a covering agent (ZnCl2) for protection, let it stand at 450℃ for 30 minutes to improve the quality of crude zinc, and use ZnCl2 to perform two aluminum reduction treatments at 680℃ and 450℃ respectively to improve the purity of zinc.
[0032] The heavy feedstock has an increased zinc content and a decreased aluminum content, with zinc used in hot-dip galvanizing slag. Since hot-dip galvanizing slag consists of dissolved iron and molten zinc in the zinc bath, the heavy feedstock acts as a melt initiator for the slag. Because the amount of melt initiator is much smaller than the amount of molten material added, the proportion of melt initiator in the entire molten liquid can be reduced by increasing the amount of molten material, thereby controlling the aluminum content in the entire molten liquid. The higher the aluminum content in the molten pool, the lower the solubility of iron in the liquid phase. Therefore, dissolving aluminum in the zinc bath can control the iron content in the zinc bath at a low level. Although the zinc content in the heavy feedstock is increased, it is still lower than the zinc content in the hot-dip galvanizing slag, which contains approximately 79% zinc. Therefore, the high proportion of zinc in the heavy feedstock can also be extracted during the hot-dip galvanizing slag treatment process, while simultaneously reducing the amount of iron dissolved in the zinc bath.
[0033] As a further supplement to the above: In step S1, the light and heavy powder groups are separated by air classification. When the particle size of the aluminized zinc slag is too small to be easily screened, the average particle size is obtained through sampling and estimation. The air force is adjusted to drive the light powder to move, the heavy powder to fall, or other relative movements of the light and heavy powders, so that the light powder is separated from the powder pile. The smaller the particle size of the aluminized zinc slag, the better the screening effect.
[0034] S11: After crushing the aluminum-zinc slag, the lightweight components are compressed into spheres of the same volume through a pelletizing process. The lightweight spheres are then further separated by mass and placed separately.
[0035] After the above steps, the small-particle-size aluminum-zinc slag is processed in smaller sizes, and the volume error has a greater impact on the quality error. When it is difficult to control the volume uniformity, the pressing and pelletizing process can be used to press the powder of the same volume into the same volume. On the one hand, it is convenient for storage and use, and on the other hand, it can make the volume more standardized and improve the differentiation accuracy.
[0036] Furthermore, in step S1, the light group and the heavy group are calculated using the average mass of a single group of particles as the unit, and a value not less than the average value is used as the dividing value to divide the light group or the heavy group.
[0037] Because under normal distribution conditions, zinc accounts for a lower proportion than aluminum, but the mass of zinc is greater than that of aluminum, the probability of extracting zinc with a high proportion is higher, using a value no less than the average value as the dividing line.
[0038] The volume of zinc dross passing through the last screen may be much smaller than the aperture of the last screen. Therefore, the volume difference of zinc dross passing through the last screen is large, so it can be directly used in the manufacture of composite aluminum-zinc-iron coagulants.
[0039] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for comprehensive utilization of tailings from aluminum-zinc smelting, characterized in that: include: Step S1, which is not less than once: After crushing the aluminum-zinc slag, it is screened through screens of different apertures. The aluminum-zinc tailings between the two screens are grouped into light group and heavy group according to the weight. S2: Place the light component in a container and add 8%-15% HCl and 20%-40% H2SO4. Immerse it in a 70-100℃ water bath constant temperature shaker for 1-3 hours. Filter the solution using ashless quantitative filter paper in the range of 40-50℃ to obtain a colorless filtrate. S3: Add 0.2%-0.8% NaOH to the colorless filtrate in step S2 and stir rapidly. The polymerization temperature is 30-50℃, the pH value is 2.5-3, and the time is not less than 2-72h. A light yellow-brown liquid is obtained and dried and ground to obtain a powdered solid. S4: Add the heavy mass to the crucible as the starting material, and add hot-dip galvanizing slag containing iron and zinc into the crucible. After melting at 680℃ and standing for 30 minutes, drain the zinc to obtain crude zinc ingots.
2. The method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: The light yellow-brown liquid obtained in step S3 is dried in an oven at 100°C for no less than 25 hours.
3. The method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: In step S1, the light and heavy groups are separated by air separation.
4. The method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: The zinc slag that has passed through the final screen is then processed together with the light-weight material in step S2.
5. A method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: In step S1, the light and heavy groups are calculated using the average mass of a single group of particles as the unit, and a value not less than the average value is used as the dividing value to classify them into light or heavy groups.
6. A method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 2, characterized in that: Including S11: After crushing the aluminum-zinc slag, the lightweight components are compressed into spheres of the same volume through a pelletizing process, and the lightweight spheres are further differentiated by mass and then placed separately.
7. A method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: In step S4, a covering agent, ZnCl2, is added to the crucible molten pool for protection.
8. A method for comprehensive utilization of aluminum-zinc smelting tailings according to claim 1, characterized in that: The process also includes step S5: adding the zinc slurry from step S4 into a pit furnace, adding a covering agent (ZnCl2) for protection, and letting it stand at 450°C for 30 minutes to improve the quality of crude zinc.